Investigating Second Language Reading Components:Reading for Different Types of Meaning - Ah-Young Kim (Working Papers in Applied Linguistics and TESOL, 2015)
The nature of second language (L2) reading ability is extremely complex and its components are yet to be agreed upon. The current study hypothesized that L2 reading ability consists of (1) reading for literal meaning (LIT), (2) reading for implied meaning with endophoric reference (IMP-EN), and (3) reading for implied meaning with exophoric reference (IMP-EX). In addition, different reading passages were assumed to affect test performance in varying degrees. Participants were 298 incoming students to an adult English as a second language (ESL) program. They took a reading placement test consisting of four reading passages and 30 items. Participants’ reading scores were analyzed using the confirmatory factor analysis (CFA) approach in structural equation modeling (SEM). Findings suggest that L2 reading ability consists of the three constructs of LIT, IMP-EN, and IMP-EX. Moreover, the three reading constructs are on a continuum with LIT having the most direct relationship between the text and the response, while IMP-EX having the most indirect relationship. However, reading passages did not have a significant influence on test performance.